Impact of the converter operating modes on line current harmonic generation - Bokoro, Ntambu Pitshou (2012)
M.Ing. === Line commutated thyristor converters are proven to be natural line harmonic currentgenerating sources regardless of their operating modes. The quality of harmonic current components induced back to the lines is commonly described to be similar under both states of operation. This however does not seem to be quite obvious as far as the aggregate harmonic current contribution to the phase inputs per operating region of thyristor converters. It becomes thus important to examine the degree of association between thyristor converter operating states and the magnitude of current harmonic pollution induced back to the input lines to subsequently establish the most current harmonic polluting region of operation. For the purpose of this study, the Nyquist-Shannon theorem, best known as the sampling theorem, whereby the converter output signal or waveform is sampled by the switching function to reconstruct the input waveform, is numerically applied in conjunction with the MatLab/Simulink 7.0 which enables the simulation of the two-quadrant operation of direct current variable speed drive (DC VSD) and that of high voltage direct current link (HVDC) converter station operation, as well as physical measurements on the twoquadrant operation of the DC VSD (Saftronics DC2L) with the aid of the digital scope meter (DSO)1200 series. However, numerical analysis based on the sampling theorem, practical measurements obtained and the MatLab/Simulink simulations indicate that the converter operating states cause a randomly distributed harmonic current generation trend in the input lines as the firing angle is increased and the most harmonic current contribution cannot be attributed to a specific region of the controlled converter firing angle.